Unexpected Hazards with Dental High Speed Drill - Kassahun Hailu; David Lawoyin; Alison Glascoe; Andrea Jackson (MDPI AG, 2017)
An expected accident can happen at any time during a routine practice in the dental office due to the types of instruments used. One of the instruments used in routine dental practice is a high speed drill and a bur. If Personal Protective Equipment (PPE) is not practiced at any time in the dental office, very serious injuries could easily happen to the clinician, staff or to the patient.